PENGARUH PENANAMAN MODAL ASING DAN PENANAMAN MODAL DALAM NEGERI SERTA PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI PROVINSI KALIMANTAN TIMUR - Jani, Rapzan; Rohaida, Eny; Djohan, Sjamsu (FORUM EKONOMI, 2015)
The purpose of this study was to determine the magnitude of the influence of foreign investment and domestic investment with goverment expenditure on the economic growth East Kalimantan province. In the current we study used multiple linear regression analysis tool, but it also aided by computer, using program SPSS 20.0. After conducting research with reference to the secondary data it was concluded there are three variabels that affect the economic growth is foreign investment and domestic investment with goverment expenditure. The result showed that simultaneous or together on the F test, the three independent variables was significant influence on economic growth East Kalimantan Province. Afterwards the t test, domestic investment variables was not significant on economic growth of East Kalimantan Province, but foreign investmen and government expenditure variabels positive influence and significant on economic growth of East Kalimantan Province..Â Keyword: foreign investment, domestic investment, government expenditure economic growth